Molecular characterization of partial gonadotropin subunits in Pangasianodon hypophthalmus (Sauvage, 1878) - Mohamed Zulperi, Zarirah; Hairudin, Muhamad Fahmie (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Pangasius hypophthalmus or Patin Siam is a fast-growing cultured catfish in the world and predominantly established for farming in Southeast Asian countries including Malaysia. In 2015, Department of Fisheries Malaysia reported the aquaculture production of pangasiid in Malaysia was 13,901.77 tonnes, down 6.32% compared to 2014. The production is restricted since the availability of the seeds and fingerlings are mostly depending from hatcheries, which could not fulfill the market demand. Therefore, study of gonadotropins (GTHs), follicle-stimulating hormone (FSH) and luteinizing hormone (LH), essential hormones for reproduction is important to know the involvement of the hormones in regulating gametogenesis in P. hypophthalmus. This study involved detection and characterization of partial genes of GTH subunits, α, FSH and LH, in P. hypophthalmus. Molecular characterization using PCR amplifications revealed that the cDNA of partial genes for α, FSHβ and LHβ in P. hypophthalmus were 443, 120 and 513 bp, respectively. Phylogenetic tree showed that P. hypophthalmus have highest similarity with Siluriformes followed by Cypriniformes. This showed that classification of GTH subunit genes of P. hypophthalmus are depending on their order and species. This is the first study of GTH subunit genes, α, FSHβ and LHβ, in P. hypophthalmus, thus the study should contribute as an initial step for a development of a better reproductive strategy in the species to increase the production in Malaysia and Asia Pacific region.